Pengaruh Perbedaan Proses Fermentasi Terhadap Karakteristik Fisik dan Kimia Kecap Ikan Sepat Siam (Trichogaster pectoralis) - Suci Indah Sari; Indah Widiastuti; Shanti Dwita Lestari (Universitas Sriwijaya, 2018)
The purpose of the research was to know physic and chemical characteristics of siamese gouramy fish sauce using three different fermentation processes. This research method used a faktorial randomized block design (FRBD) with two treatment factor and done with three replications. The factor treatment were consists of a type of fermentation (spontaneous, pedioccus halophilus, enzyme papain) and fermentation time (30. 60. 90 day). This research shows that the different of fermentation type and fermentation time had significant effect on yield, pH, ash content, protein content, tvb and interaction between fermentation type and fermentation time had significant effect on chrome. The best product is papain enzyme addition and long fermentation during 90 days that produce the product had yield (58.8%), pH (6.04), ash content (23.82%), protein content (2.46 mg/mL), tvb (94.58 mg/100mg), viskositas (0.65 dPas), lightness (26.6), chrome (2.17), and hue (41)